2022
DOI: 10.4269/ajtmh.21-0316
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Asymptomatic Malarial Anemia and Association with Early Conversion from Asymptomatic to Symptomatic Infection in a Plasmodium falciparum Hyperendemic Setting in Cameroon

Abstract: Asymptomatic malarial parasitemia is highly prevalent in Plasmodium falciparum endemic areas and often associated with increased prevalence of mild to moderate anemia. The aim of this study was to assess the prevalence of anemia during asymptomatic malaria parasitemia and its interplay with persistent infection in highly exposed individuals. A household-based longitudinal survey was undertaken in a malaria hyperendemic area in Cameroon using multiplex nested polymerase chain reaction to detect plasmodial infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 45 publications
2
19
0
Order By: Relevance
“…Considering 10–14-year-olds for example, this group had a higher prevalence of P. falciparum infection than young children or adults, and over 80% of anaemia was associated with malaria infection. The role of malaria in the burden of anaemia in Cameroon may extend even to asymptomatic malaria infection as a recent longitudinal study across multiple villages in Cameroon’s Central Region found asymptomatic malaria infection (diagnosed by PCR) was associated with 69.2% of anaemia in the study population [ 41 ]. Despite this association, the relationship between anaemia and malaria in children remains complex.…”
Section: Discussionmentioning
confidence: 99%
“…Considering 10–14-year-olds for example, this group had a higher prevalence of P. falciparum infection than young children or adults, and over 80% of anaemia was associated with malaria infection. The role of malaria in the burden of anaemia in Cameroon may extend even to asymptomatic malaria infection as a recent longitudinal study across multiple villages in Cameroon’s Central Region found asymptomatic malaria infection (diagnosed by PCR) was associated with 69.2% of anaemia in the study population [ 41 ]. Despite this association, the relationship between anaemia and malaria in children remains complex.…”
Section: Discussionmentioning
confidence: 99%
“…The longevity of asymptomatic falciparum malaria has been studied in several settings with the prevalence in naturally occurring infections ranging from 2 months in Vietnam (8), 5–6 months in a longitudinal study in Ghana (13) and 6–9 months in Myanmar (14). Over the course of our 3-month study, we have shown that there is a high rate of persistent asymptomatic parasite carriage in Cameroon (43). Mathematical modelling of existing data indicates that asymptomatic P. falciparum infections could last for as long as 13-years (68).…”
Section: Discussionmentioning
confidence: 80%
“…(45). Genotyping of msp2 gene was performed by nested PCR on P. falciparum PCR positive samples as previously described (43,46).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, E03 [ 131 ] showed that rhesus macaques infected with P. coatneyi develop chronic infections after receiving subcurative artemether treatment and that they recapitulate the decrease in haemoglobin levels characteristic of persistent infection in humans [ 45 , 488 ]. A recent study with kra monkeys infected with P. knowlesi showed evidence of a similar phenotype, but without the administration of subcurative anti-malarial treatment (see E07 below) [ 268 ].…”
Section: Establishing Academic Environments For Nhp Research With Com...mentioning
confidence: 99%